Influence of gender on pacing adopted by elite triathletes during a competition - Le Meur, Y.; Hausswirth, C.; Brisswalter, J.; Bernard, T. (14th annual Congress of the European College of Sport Science, Oslo/Norway, June 24-27, 2009, Book of Abstracts, 2009)
The aim of the present research was to improve the description of the pacing strategies adopted by female and male elite triathletes during a World Cup triathlon and to discuss possible factors influencing the self-selection of such strategies. Methods Twelve elite triathletes (6 females, 6 males) performed three maximal tests: an all-out 400-m front-crawl to determine their swimming maximal heart rate (swimming HRmax), an incremental cycling test during which power output (PO), heart rate (HR), at ventilatory thresholds (VT1, VT2), maximal aerobic power (MAP) were assessed, and an incremental running test to evaluate their maximal running HRmax. Throughout a World Cup short distance competition, speed and HR were measured. The amount of time spent below 10% of PO (zone 1), between 10% MAP and PO at V1 (zone 2), between PO at VT1 and VT2 (zone 3), between PO at VT2 and MAP (zone 4) and above MAP (zone 5) was analyzed during the cycling leg. Results Swimming and running speeds decreased similarly for both genders (P < 0.05) and HR values were similar through the whole race (92±2% and 92±3% HRmax for women and men, respectively). The distribution of time spent in the 5 intensity zones during the cycling leg was the same for both genders (17 ± 5% and 17 ± 3% for zone 1, 36 ± 5% and 31 ± 5% for zone 2, 13 ± 2% and 19 ± 7% for zone 3, 13 ± 6 and 14 ± 3% for zone 4, 22 ± 2% and 19 ± 2% for zone 5 for women and men, respectively). Men`s speed and PO decreased after the first bike lap (P < 0.05) and women spent more relative time above MAP in the hilly sections (45±4% vs. 32±4%). Men`s running speed decreased significantly over all the circuit, whereas women slowed only over uphill and downhill sections (P < 0.05). Conclusion The main finding of this study was that both female and male elite triathletes adopted similar positive pacing strategy during swimming and running legs. On the contrary, men pushed the pace toughly during the swim-to-cycle transition in contrary to women and female triathletes were more affected by changes in slope during both cycling and running phases. These effects of gender on pacing may have strong implications for the differentiation of training for female and male elite triathletes. References Hausswirth, C., Brisswalter, J. Strategies for improving performance in long duration events: Olympic distance triathlon. Sports Med. 2008;38:881-91. Vleck VE, Bürgi A, Bentley DJ. The consequences of swim, cycle, and run performance on overall result in elite olympic distance triathlon. Int J Sports Med. 2006;27:43-8. Vleck VE, Bentley DJ, Millet GP, Bürgi A. Pacing during an elite Olympic distance triathlon: Comparison between male and female competitors. J Sci Med Sport. 2007;11:424-32.